Pengaruh Jumlah Pengunjung, Ulasan Produk, Reputasi Toko Dan Status Gold Badge pada Penjualan Dalam Tokopedia - Nurul, Mochammad; Soewarno, Noorlailie; Isnalita, Isnalita (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p14, 2019)
This study aims to find out the influence of some items in Tokopedia's product pages (product popularity, customer reviews, store reputation, and gold badges) toward sales. We were using quantitative as the research design, descriptive research analysis and correlation category. We collect data and tested it using the multiple regression analysis method with SPSS version 21. The results show that product review is the most important variable than other variables such as popularity, reputation, and gold merchants. Keywords : C2C, Marketplace, Online, Sales, Tokopedia